PERANAN KOMUNIKASI SOSIAL DALAM PELAKSANAAN TUGAS BABINSA WILAYAH KORAMIL 02 KODIM 1421 - KARTINI KARTINI; ZOHRAH N (Fakultas Dakwah dan Komunikasi, 2018)
Social communication carried out by Babinsa in its duty area is very instrumental as a means of communication to maintain and improve good relations between Babinsa and community elements in Minasate'ne District and as a means of socialization in conveying the Army leadership's vision, mission and policies and being able build community motivation in order to support the Army Territorial Development activities, especially the Babinsa task in the field of national defense. The results of the study through primary data collection showed the community in the district Minasate'ne gave a very positive assessment of the implementation of Babinsa's duties in the area of duty because they felt very helped and motivated by the existence of Babinsa with various activities pioneered by Babinsa such as regional security affairs with the implementation of Self-Defense (Poskamling) and special efforts to increase production rice, corn and soybeans in order to realize national food self-sufficiency in the district area Minasate'ne. Finally, there are several factors that influence the success of the implementation of Babinsa duties in the district. Minasate’ne, includes supporting factors and inhibiting factors.